29Si–1H IMPACT HMBC: a suitable tool for analyzing silylated derivatives. (13th February 2013) - Farjon, Jonathan; Giros, Audrey; Deloisy, Sandrine; Blanco, Luis; Hannedouche, Jérôme; Schulz, Emmanuelle; Merlet, Denis
<x xml:space="preserve">Abstract</x> A modified version of the IMPACT heteronuclear multiple bond correlation (HMBC) has allowed the characterization of an organosilane and a tetrasilylated yttrium complex. With the help of this sequence, an average gain in sensitivity close to 2 has been obtained compared with the standard HMBC experiment for disilanes as well as for yttrium complexes containing silylated ligands. This modified version of this long‐range correlation experiment opens the way for following kinetics in the range of a fraction of a minute and to study by NMR low concentrated samples and low abundant nuclei. Copyright © 2013 John Wiley & Sons, Ltd.